Legal Framing of Artificial Intelligence - Belhout, Ibrahim (Journal of Legal Studies and Researches, 2024)
The private system of liability for defective products appears to be able to accept (AI) as a product, along with worthwhile (AI) ethics. However, its legitimacy remains debated. It appears that the intellectual property system is limited to protecting the algorithm. The issue of transparency remains the most controversial in the field of framing (AI).